(untitled) (World Bulletin of Management and Law, 2025)
This article examines the constitutional and legal foundations of the institution of advocacy in the Republic of Uzbekistan. It highlights the historical development of the advocacy system, its role in ensuring the protection of human rights and freedoms, as well as its importance in the implementation of justice. Special attention is given to the legislative reforms aimed at strengthening the independence and effectiveness of the institution of advocacy.